ANALYSE DES DETERMINANTS DE L’EFFICACITE ENERGETIQUE DANS L’ESPACE UEMOA - Wadjamsse Beaudelaire Djezou (European Scientific Journal, ESJ, 2013)
﻿﻿Energy saving strategies are key means for developing countries, non-oil producers, to fight against energy dependency and its huge share in national budget. In this perspective, this paper investigates the determinants of energy efficiency in WAEMU countries in order to ensure a sustainable growth. To this end, we used the panel data methodology especially a robust fixed effects model in the form of error correction model. Firstly, we found a U relationship between energy intensity and GDP. Secondly, the structure of the WAEMU economies is a significant determinant of their energy efficiency level in the sense that industrial and service sectors significantly reduce their energy intensity. However, the study shows that public sector activities and households’ social and economic behaviors are energy intensive activities. In the same way, the stock of capital is composed of less energy saving technologies since it positively affects the energy consumption per unit of output. Finally, this paper reveals significant differences between WAEMU countries energy intensities.